Synthesis photophysical studies of some furfurylnitrones: high-ly selective chemosensors for Zn2+ and DFT studies - Dhineshkumar, Ezhumalai; Iyappan, Mathivanan; Ganapathi, Rajendran; Anbuselvan, Chinnadurai (International Journal of Advanced Chemistry, 2018)
New aldonitrones(1-4) were synthesized and characterized by UV-vis, fluorescence, FT-IR, 1H and 13C NMR spectral analyses. The absorption and fluorescence sensing spectra of the compounds were precise in different polarity of solvent. The solvent polarity parameters have been used to propose a quantitative approach towards the reliable stability of the electronic ground and excited state species. Photochemical behaviors of the compounds were analyzed by applying multi-linear correlation methods. The characterized compounds 1-4 show a chemosensing detection of zinc ion in aqueous solution. Besides, the fluorescence spectroscopic responses were reversible when the Zn2+chelating reagentEDTANa2.The phenomenon proves that these compounds to show a sensitivity â€œon-offâ€ sensor for Zn2+.Further, to recognize the molecular structure, electronic and optical properties and DFT calculations of the molecules were formed.
Keywords: Aldonitrones; Solvaotochromic Absorption; Zn2 Sensor; DFT.